IMPLEMENTASI PERIZINAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) TERHADAP IZIN PERKEBUNAN KELAPA SAWIT ROKAN HULU 2019-2023 - Wijaya, Agus; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Licensing is important to ensure that permitted activities comply with applicable legal, health, safety and environmental standards, as well as to maintain public interests and community order. This research aims to find out how important licensing is and how much it is needed in society. Looking at the obstacles faced by the Rokan Hulu Regency Investment and One-Stop Integrated Services Service (DPMPTSP), there are still business actors who do not take care of plantation permits in (DPMPTSP) and are aware of the implementation of one-stop integrated services at the One-Stop Investment and Integrated Services Service. Rokan Hulu Regency Door as a form of public service. The research method used is descriptive qualitative. The results of this research reveal that the problem of compliance with rules and regulations in the oil palm plantation sector in Rokan Hulu Regency is a complex issue and requires serious attention. Even though there are some businesses that have complied with regulations and paid fees, there are still many that do not have permits or do not comply with applicable regulations. This has negative impacts such as environmental degradation, social conflict and economic losses for society. Stronger efforts are needed from local governments to enforce regulations and provide adequate incentives for business actors who comply with regulations. Keywords : Licensing, Policy, Implementation.